Exploring the potential of digital resources as a source of social support in first time pregnancy - Nikki Newhouse (Frontiers Media S.A., 2015)
Background First-time pregnancy is a significant life event and holistic maternal wellbeing is important. Dominant social narratives state that pregnancy is a time of fulfilment and stability but many women report feeling otherwise. Healthcare prioritises generic information relating to physical health and psychological support is often overlooked. Up to 20% of women experience clinical levels of anxiety or depression during pregnancy [1] and poor antenatal wellbeing is associated with negative outcomes for mother and baby [2]. Research suggests that standard antenatal care often does not meet women's wellbeing needs [3] and that poor antenatal wellbeing in uncomplicated first time pregnancy is connected to issues of identity change and low perceived social support [4]. Social support in first time pregnancy is associated with better maternal health, relationship satisfaction, child outcomes and coping [5]. Satisfaction with social support protects against postpartum depressive symptoms and has a positive association with parental self-efficacy [6]. HCI research is starting to explore technology's growing role in the experience of pregnancy [7]. Pregnant women seek out support in navigating new responsibilities through social connection offered via digital media. Internet and smartphone access and usage is ubiquitous within this group, and research confirms that pregnant women routinely source information and support via the Internet, particularly when they deem their antenatal care to be insufficient [8]. The potential for online resources to provide social connectedness and support to pregnant women is profound [9]. Pregnancy has unquestionably 'gone wired' [10]. However, a minority of antenatal digital resources focus specifically on social support: peer-to-peer contact is usually unmoderated and offered as an add-on to the main event of 'pushed-out' information dissemination. This is despite women consistently stating a desire to connect with other women 'like them' and acknowledgement of the benefits of well-designed online peer support in parenting. Aim This research seeks to answer the following question: Can online peer support during first time pregnancy improve subjective wellbeing? An exploratory approach is being followed with a focus on user studies guiding the development of a working prototype of an online peer support resource. Method / Results In order to answer the research objective, several sub-problems need to be addressed. The project follows the Medical Research Council's iterative framework for the development of complex interventions [11]. Goal1: Evaluation of current evidence. Methods: The current state of the multidisciplinary evidence for the potential for digital resources to provide social support in first time pregnancy will be evaluated by means of a critical interpretive synthesis of the relevant literatures, to include computer science, digital sociology, perinatal care, wellbeing. Goal 2: Conceptual clarification of 'wellbeing' in first time pregnancy. Methods: (i) Conduct semi-structured interviews with pregnant women, mothers and health professionals; (ii) Analysis of the interview data will determine key features of antenatal wellbeing. Goal 3: Understanding what characteristics define those who are willing to engage with online peer support. Methods: (i) Conduct semi-structured interviews with pregnant women, mothers and health professionals; (ii) Analysis of the interview data will determine which group/s of women might find online peer support more useful than others. Goal 4: What are the user requirements of those who are willing to engage with online peer support? Methods: (i) Conduct semi-structured interviews with pregnant women, mothers and health professionals; (ii) Analysis of the interview data will provide basic user requirements which will inform the development of a preliminary prototype. (iii) Test these basic user requirements in subsequent participatory design development cycles. Goal 5: Understanding the impact of the intervention. Methods: (i) Evaluate the prototype 'in the wild', incorporating measures of satisfaction, acceptability and adherence. (ii) Conduct interviews with users. Findings from the critical interpretive synthesis and semi-structured interviews will be presented. Conclusions First-time pregnancy is a time of huge physical and emotional change and women often need support. One way of providing this is to provide wellbeing information. However, pregnant women are bombarded with information, much of it generic, conflicting or anecdotal. Large numbers of women look for information and advice online, increasingly engaging with alternative forms of 'expert' information, in the form of other people's experiences. This context provides a unique opportunity for digital resources to act as preventative medicine: bringing women together in a safe online environment allows them to speak freely, develop practical skills and feel supported as they become parents. This in turn relieves healthcare burden by preventing negative maternal and neonatal outcomes. This project will determine the context-driven user needs and requirements of a unique group of people and demonstrates the importance of a multidisciplinary approach to the development of pragmatic digital health solutions.